Ragam Dieksis dalam Dunia Robohnya Surau Kami: Studi Kasus pada Karya A.A. Navis - Wardedy Rosi; Ila Maghfiroh (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Language is a communication tool that connects messages between the speaker and the listener through various pragmatic contexts such as interpersonal relationships, event backgrounds, discussion topics, and communication media. Lexicons in speech often contain numerous references, especially deictic lexicons that rely on context for accurate interpretation. This research employs a qualitative descriptive approach to explore the various styles of deictic language in the short story